Microstructure of Aged 238Pu-doped La-monazite Ceramic and Peculiarities of its X-ray Emission Spectra. (2020) - Shiryaev, Andrey A.; Burakov, Boris E.; Yapaskurt, Vasily O.; Egorov, Alexander V.; Vlasova, Irina E.
Abstract: New data on microstructure of 16 years old (La, Pu)PO4 monazite ceramics doped with 8.1 wt% of 238 Pu are presented. It is shown that the sample consists from at least two phases differing in La/Pu ratio and small precipitates of Pu-phosphate. Possible mechanisms of the compositional heterogeneity are discussed. Formation of Pu-containing rhabdophane after sample storage in air is observed. This phenomenon together with gradual mechanical destruction of the ceramic pellet formation of submicron particles will likely increase rate of radionuclides loss from the monazite-based waste form. X-ray emission lines produced by recoil uranium ions from Pu decay are analysed. It is suggested that careful examination of their relative intensities may provide important information about behaviour of "hot" recoils in nuclear waste forms.